Word and text processing in acquired prosopagnosia. Issue 2 (1st July 2015) - Hills, Charlotte S.; Pancaroglu, Raika; Duchaine, Brad; Barton, Jason J. S.
<x xml:space="preserve">Abstract</x> Objective A novel hypothesis of object recognition asserts that multiple regions are engaged in processing an object type, and that cerebral regions participate in processing multiple types of objects. In particular, for high‐level expert processing, it proposes shared rather than dedicated resources for word and face perception, and predicts that prosopagnosic subjects would have minor deficits in visual word processing, and alexic subjects would have subtle impairments in face perception. In this study, we evaluated whether prosopagnosic subjects had deficits in processing either the word content or the style of visual text. Methods Eleven prosopagnosic subjects, 6 with unilateral right lesions and 5 with bilateral lesions, participated. In the first study, we evaluated their word length effect in reading single words. In the second study, we assessed their time and accuracy for sorting text by word content independent of style, and for sorting text by handwriting or font style independent of word content. Results Only subjects with bilateral lesions showed mildly elevated word length effects. Subjects were not slowed in sorting text by word content, but were nearly uniformly impaired in accuracy for sorting text by style. Interpretation Our results show that prosopagnosic subjects are impaired not only in face recognition but also in perceiving stylistic aspects of text. This supports a modified version of the many‐to‐many hypothesis that incorporates hemispheric specialization for processing different aspects of visual text. Ann Neurol 2015;78:258–271